Lean behavior in implementing lean process management - A. Perumal, Puvanasvaran; Megat Ahmad, Megat Mohamad Hamdan; Tang, Sai Hong; Muhamad, Mohd Razali; Hamouda, Abdel Magid Salem (INSInet Publication, 2009)
Lean is one of the popular concept has been practiced in most company. However, there are a lot of companies who implement lean are not realized whether lean level of company is improve or relegate. Thus, it is important to inspect the lean result after implementation of lean. So, this study presents to make the result comparison for lean behavior after implement lean for one year thru People development system which improves problem solving capabilities of people in eliminating wastages. Furthermore, the importance of problem solving capabilities of people in implementing lean process management also will be discussed. The survey was conduct in an aero composite manufacturer kitting department. Self-administered questionnaire has been selected to be the survey instrument. These questionnaires were distributed to 45 employees work in the kitting department. Results of feedback are collected and analyzed by using the Statistical Package for Social Science (SPSS) software version 13. The outputs of the analysis were in the form of index values, percentages and hypothesis testing. The result showed the improvement on lean behavior with the help of people development system implementation which enhance the people capabilities in eliminating wastages. These are supported by comparing the survey results on lean behavior for beginning and end of the year with the monitoring of real life data on the case study.